1976
DOI: 10.1111/j.1600-051x.1976.tb00040.x
|View full text |Cite
|
Sign up to set email alerts
|

The possible pathogenesis of gingival recession

Abstract: Stages in the pathogenesis of gingival recession were observed in rats in which pocketing had been induced by replacement of natural incisors with dental implants. Suitable conditions were thus created on the palatal aspect of the implant sockets for recession to occur. The recession process was examined at intervals by taking transverse serial sections. In the epithelial and connective tissues deep to the receding margin, morphological changes were seen which apparently lead to cleft formation and recession. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(69 citation statements)
references
References 6 publications
3
45
0
14
Order By: Relevance
“…2,5,21,30,33 The influence of age on GR frequency increase should probably be explained by the accumulation of numerous recession-contributing factors in time. 6,21,30,33,36,37 According to our research, a higher frequency of gingival recession and greater lesion advancement were observed in the older age group (65-74 years). Statistically significantly higher values of gingival recession depth compared to the younger group were obtained regardless of the localization of the analyzed pathology in the oral cavity.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…2,5,21,30,33 The influence of age on GR frequency increase should probably be explained by the accumulation of numerous recession-contributing factors in time. 6,21,30,33,36,37 According to our research, a higher frequency of gingival recession and greater lesion advancement were observed in the older age group (65-74 years). Statistically significantly higher values of gingival recession depth compared to the younger group were obtained regardless of the localization of the analyzed pathology in the oral cavity.…”
Section: Discussionsupporting
confidence: 52%
“…4 According to other authors, the areas with gingival deficit in terms of thickness are more susceptible to GR development due to a smaller amount of connective tissue in this site and thus a faster inflammation progression due to the factors that induce and contribute to gingival recession development. 36,37,39 This data may also explain more frequent GR development on the lingual surfaces of bottom teeth at older age. According to our research, a significantly higher frequency of gingival recession on lingual surfaces in older individuals was observed.…”
Section: Discussionmentioning
confidence: 75%
“…However, with regard to the soft tissues, the finding of recessions is not an infrequent event [6]. The gingival recession can be determined by plaque-induced periodontal inflammation and/or trauma during tooth brushing [7]. If a control of these factors is performed, eliminating the etiological factor of inflammation or performing proper tooth brushing, the progression of the recession is avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Pain, swelling 10 and infection 50 , mucosal or gingival trauma, chipped or fractured tooth, increased salivary flow, calculus build-up, foreign body granulomas 11,13 or allergies, hypertrophic scarring (fig 4), Ludwig"s Angina. 14, 24, 25, 26, bleeding into the pharynx and airway obstruction in anaesthesia 15 , airway problems secondary to swelling of the tongue.…”
Section: Other and Later Complications Includementioning
confidence: 99%